A Body Shape Index and Pulse Wave Velocity: strong markers of coronary artery calcification in dyslipidemic patients (Research, Society and Development, 2022)
Objective: To identify, among different Cardiovascular Risk Predictors (CVRP), which have the best associations with Coronary Artery Calcification (CAC). Methodology: Cross-sectional study, with dyslipidemic (age >18), to investigate the association between CVRP [anthropometrics, biochemicals, clinicals, Ankle-Brachial Index (ABI), arterial stiffness] and Coronary Calcium Score (CCS), which was classified according to (1) CCS=0, CCS=1-100, CCS>100, (2) CCS=0, CCS=1-99, CCS=100-299, CCS>300 and (3) dichotomous (CCS=0 or CCS>P75/CCS>100). Bivariate descriptive and inferential statistics were performed. ROC curves estimated the CAC risk of the independent variable. The univariate logistic regression model identified the probability of CAC and established the sensitivity and the specificity of each predictor and the multivariate identified higher risk variables and their respective Odds Ratio (OR). Results: 180 patients evaluated, 65.5% were women, mean age 59.8. CAC was associated with Waist Circumference (p=0.03), A Body Shape Index Risk-ABSIR (p